2017
DOI: 10.1038/s41467-017-01694-y
|View full text |Cite
|
Sign up to set email alerts
|

Redox-independent chromium isotope fractionation induced by ligand-promoted dissolution

Abstract: The chromium (Cr) isotope system has emerged as a potential proxy for tracing the Earth’s atmospheric evolution based on a redox-dependent framework for Cr mobilization and isotope fractionation. Although studies have demonstrated that redox-independent pathways can also mobilize Cr, no quantitative constraints exist on the associated isotope fractionations. Here we survey the effects of common environmental ligands on the dissolution of Cr(III)-(oxy)hydroxide solids and associated Cr isotope fractionation. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 66 publications
(125 reference statements)
2
53
0
Order By: Relevance
“…A small extent of reduction would lead to low δ 53 Cr values, while quantitative reduction would lead to similar to seawater values (Wang et al, 2016). Direct incorporation of organic acid and/or siderophore-bound Cr(III), as recently proposed by Saad et al (2017) to have a significant impact on the Cr cycle via their release from the continents to the oceans, can also be considered to play a role in the marine biogenic calcification processes as these compounds have been shown to carry isotopically heavy Cr(III) compositions that are reached through redox-independent chromium isotope fractionation induced by ligand-promoted Cr(III) dissolution on land.…”
Section: Shells -Chromium Isotope Compositions and Chromium Concentramentioning
confidence: 99%
See 2 more Smart Citations
“…A small extent of reduction would lead to low δ 53 Cr values, while quantitative reduction would lead to similar to seawater values (Wang et al, 2016). Direct incorporation of organic acid and/or siderophore-bound Cr(III), as recently proposed by Saad et al (2017) to have a significant impact on the Cr cycle via their release from the continents to the oceans, can also be considered to play a role in the marine biogenic calcification processes as these compounds have been shown to carry isotopically heavy Cr(III) compositions that are reached through redox-independent chromium isotope fractionation induced by ligand-promoted Cr(III) dissolution on land.…”
Section: Shells -Chromium Isotope Compositions and Chromium Concentramentioning
confidence: 99%
“…Such high D Cr values observed in biogenic carbonates produced by different marine organisms point to a strong biological control over the incorporation of Cr from seawater into CaCO 3 skeletons, where it could be incorporated either as Cr(III) and/or Cr(VI) depending on species-specific redox cycling of Cr (cf. Wang et al, 2016;Semeniuk et al, 2016) and/or, as recently suggested, directly assimilated as 4916 R. Frei et al: A systematic look at chromium isotopes in modern shells organic ligand-bound Cr during biological uptake (Saad et al, 2017). It is too premature to compare the biogenic distribution coefficients with abiogenic values, simply because there is a lack of suitable modern seawater-carbonate pairs from which such values could be calculated.…”
Section: Individual Shells -Chromium Distribution Coefficients (D Cr mentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidation of Cr(III) by Mn oxides exhibits fractionations [Δ 53 Cr = δ 53 Cr(VI)–δ 53 Cr(III)] ranging between –0.5‰ and 1.0‰ (Bain & Bullen, ; Joshi, ; Joshi et al., ), but these results have not been evaluated in the peer‐reviewed literature. Nevertheless, the small fractionations reported for oxidation of Cr(III) to Cr(VI) are in the same range as redox‐independent Cr(III) fractionations (Babechuk et al., ; Saad et al., ), thus demonstrating the challenge of distinguishing redox‐dependent and redox‐independent controls on Cr isotope variability in the Earth's exogenic system.…”
Section: Discussionmentioning
confidence: 94%
“…Saad et al. () reported epsilon values for ligand‐promoted dissolution of amorphous Cr(OH) 3 (ϵnormalCrfalse(normalIIIfalse)normalCrfalse(normalVIfalse) ) ranging between ~ –0.3 and +1.3‰. Babechuk et al.…”
Section: Discussionmentioning
confidence: 99%